Effect of surface texturing on the durability of concentrated polymer brushes. (March 2021) - Watanabe, Seiya; Kodama, Eri; Sakakibara, Keita; Sasaki, Shinya; Tsujii, Yoshinobu
Abstract: Concentrated Polymer Brushes (CPBs) have great potential to improve tribological properties under severe sliding conditions, even at the macroscopic scale, and thus are expected to apply to mechanical sliding components. However, the durability of CPBs has remained as a challenge for industrial applications. Here, we focused on a combination of CPBs and surface texturing technology to increase their durability. In this work, the effects of surface texturing, such as geometrical patterns on the durability of CPBs under severe sliding conditions, were investigated. The results demonstrate that applying a surface texture onto a substrate of CPBs can effectively improve the friction durability of CPBs because the polymers inside the textures, which have a locally milder contact condition, are prone to survive. By applying an appropriate surface texture, we achieved up to a 36% increase in durability. Highlights: Concentrated Polymer Brushes (CPBs) have excellent frictional properties (lower than 0.03 in friction coefficient). Applying a groove texture onto the substrate of CPBs increases their friction durability up to 36% compared to nontextured CPBs.